Calculating and Improving ROI in Software and System Programs. - CANTOR, MURRAY (Communications of the ACM, 2011)
The article discusses methods of calculating return on investment in software and systems. It notes that the measurable value of incomplete software and system programs is not widely or well understood. A method which uses Monte Carlo simulation to estimate the costs and benefits of incomplete programs is described. Techniques for specifying the costs of a development effort are described in the context of software economics and portfolio management. Topics such as deterministic net present value, equity option methods, and intellectual capital assets are also addressed.